Can smartphones serve as an instrument for driver behavior of intelligent transportation systems research? A systematic review: Challenges, motivations, and recommendations - Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Can smartphones serve as an instrument for driver behavior of intelligent transportation systems research? A systematic review: Challenges, motivations, and recommendations by Salem Abdullah Salem Garfan